Serum GFAP differentiates Alzheimer's disease from frontotemporal dementia and predicts MCI-to-dementia conversion. Issue 6 (27th April 2022) - Oeckl, Patrick; Anderl-Straub, Sarah; Von Arnim, Christine A F; Baldeiras, Inês; Diehl-Schmid, Janine; Grimmer, Timo; Halbgebauer, Steffen; Kort, Anna M; Lima, Marisa; Marques, Tainá M; Ortner, Marion; Santana, Isabel; et al.
Abstract : Objective: Reactive astrogliosis is a hallmark of Alzheimer's disease (AD) and frontotemporal dementia (FTD) but differences between the diseases and time course are unclear. Here, we used serum levels of the astroglial marker glial fibrillary acidic protein (GFAP) to investigate differences in patients with AD dementia, mild cognitive impairment (MCI)-AD and behavioural variant FTD (bvFTD). Methods: This multicentre study included serum samples from patients diagnosed with AD dementia (n=230), MCI-AD (n=111), bvFTD (n=140) and controls (n=129). A subgroup of patients with MCI-AD (n=32) was longitudinally followed-up for 3.9±2.6 years after sample collection. Serum levels of GFAP, neurofilament light chain (NfL) and pTau181 were measured by Simoa (Quanterix) and Ella (ProteinSimple). Results: In total, samples from 610 individuals from four clinical centres were investigated in this study. Serum GFAP levels in AD dementia were increased (median 375 pg/mL, IQR 276–505 pg/mL) compared with controls (167 pg/mL, IQR 108–234 pg/mL) and bvFTD (190 pg/mL, IQR 134–298 pg/mL, p<0.001). GFAP was already increased in the early disease phase (MCI-AD, 300 pg/mL, IQR 232–433 pg/mL, p<0.001) and was higher in patients with MCI-AD who developed dementia during follow-up (360 pg/mL, IQR 253–414 pg/mL vs 215 pg/mL, IQR 111–266 pg/mL, p<0.01, area under the curve (AUC)=0.77). Diagnostic performance of serum GFAP for AD (AUC=0.84, sensitivity 98%, specificity 60%, likelihood ratio 2.5) was comparable to serum pTau181 (AUC=0.89, sensitivity 80%, specificity 87%, likelihood ratio 6.0) but superior to serum NfL (AUC=0.71, sensitivity 92%, specificity 49%, likelihood ratio 1.8). Conclusions: Our data indicate a different type of reactive astrogliosis in AD and bvFTD and support serum GFAP as biomarker for differential diagnosis and prediction of MCI-to-dementia conversion.